Pathways to Internationalize Brazilian Journals of Psychology - Gamba,Estêvão C. (2015)
AbstractThe science of psychology has been developing in the country of Brazil over the last 50 years. Nonetheless, most of the science in this field is published only in Brazilian journals. Overall, Brazil has yet to share its science with the international community. The potential to internationalize the science generated by Brazilian psychologists exists, though. One way would be to scale up the publication of Brazilian psychologists in international journals. Another way would be to internationalize the existing Brazilian journals. With regard to the latter possibility, a metric analysis of scientometrics databases suggests that the reasons for the low impact of articles published in Brazilian journals are manifold, but the low performance is mainly explained by the scarce employment of the lingua franca-English language-in the articles. This article discusses the role that SciELO, a Brazilian scientific publisher, has played in indexing and assisting the best Brazilian psychology journals in raising their horizons, in terms of internationalizing their output, while at the same time serving as an instrument of promotion for national studies of psychology within the country of Brazil.